Smart Tourism Development for Recreation in Pesanggrahan Sangga Buana Urban Forest, South Jakarta - Luthfia Ainur Rahma; Hermawan, Rachmad; Eva Rachmawati (Media Konservasi, 2024)
Urban forest is a form of green open space in the urban area. The use of information and communication technology based on smart tourism is an important factor in providing facilities for recreational areas. This research aims to formulate smart tourism-based development at PSBUF for recreation based on resources, management and preferences of visitors and the surrounding community. Data collection methods used were literature studies, field observation, questionnaires, and interviews. The data analysis used were qualitative, quantitative descriptive, and SWOT. Pesanggrahan Sangga Buana Urban Forest (PSBUF) has the potential to develop smart tourism-based facilities for recreation. Standard recreational facilities are available in the form of prayer rooms, toilets, gazebos, jogging tracks, parking lots, badminton courts and football fields. Urban forest management is carried out by EFG Sangga Buana with supervision by the DKI Jakarta Parks and Urban Forest Service. EFG Sangga Buana strives to preserve the environment in the DKI Jakarta area with facilities that do not disturb the surrounding ecosystem. The existence of jogging tracks and sports fields is still lacking. The biggest motivation for visiting the urban forest is to refresh the mind from daily boredom. Public facilities that are really needed are rubbish bins. Respondents need for smart tourism facilities in the form of CCTV is the highest. Recommendations for the development of facilities are optimizing potential, maximizing management cooperation, increasing PSBUF promotions, and optimizing coordination between managers.